Iranian Foreign Policy Towards Africa: Reality and Future - Muna Hussein Obaid, Prof. Dr. (lark, 2026)
Abstract The African continent has received significant attention from many regional and international powers. Iran has been one of the countries seeking to open up horizons of cooperation with most countries on the continent, even making it a priority in its foreign policy. Since the 1960s, Iran has sought to establish diplomatic relations with most African countries. Even after the Islamic Revolution in Iran in 1979, relations expanded, particularly after Iran affirmed, through its foreign policy, that it stands with African countries seeking to free themselves from colonial control. This may have led to a significant rapprochement between Iran and most countries on the continent. Iranian interest in Africa reached its highest levels during the era of Iranian President Mahmoud Ahmadinejad, who placed it on his list of priorities. It constitutes a key point in the orientations of his foreign policy, which aimed to develop its relations with African countries on all political, economic, military, and even security levels. Its policy toward Africa has not changed even after Presidents Hassan Rouhani and Ebrahim Raisi assumed power in Iran.